2021
DOI: 10.3390/nu13113812
|View full text |Cite
|
Sign up to set email alerts
|

Why We Eat Too Much, Have an Easier Time Gaining Than Losing Weight, and Expend Too Little Energy: Suggestions for Counteracting or Mitigating These Problems

Abstract: The intent of this review is to survey physiological, psychological, and societal obstacles to the control of eating and body weight maintenance and offer some evidence-based solutions. Physiological obstacles are genetic and therefore not amenable to direct abatement. They include an absence of feedback control against gaining weight; a non-homeostatic relationship between motivations to be physically active and weight gain; dependence of hunger and satiation on the volume of food ingested by mouth and proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 115 publications
(132 reference statements)
0
7
0
3
Order By: Relevance
“…Eating habits contribute to overweight and obesity [49,50]. Encouraged by an obesogenic environment, overeating is commonly triggered by situational factors such as food novelty or variety, social company (eg, eating with certain people), affect emotional states (which trigger emotional eating), and distractions (eg, concurrent tasks) [30,[50][51][52][53]. Other studies have suggested that people at risk for obesity exhibit hyperresponsivity in the neural reward system to calorie-dense foods, which is associated with increased food consumption [54].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Eating habits contribute to overweight and obesity [49,50]. Encouraged by an obesogenic environment, overeating is commonly triggered by situational factors such as food novelty or variety, social company (eg, eating with certain people), affect emotional states (which trigger emotional eating), and distractions (eg, concurrent tasks) [30,[50][51][52][53]. Other studies have suggested that people at risk for obesity exhibit hyperresponsivity in the neural reward system to calorie-dense foods, which is associated with increased food consumption [54].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Since the thesis of this review is that gastro-intestinal signals are the principal guides to human appetite and energy balance, how should individuals implement this guidance?. Here is a list of suggested options: Resist environmental pressure to overeat whether caused by social facilitation during holidays, highly palatable foods, or commercial pressure to eat oversized portions in restaurants 73 . Follow “hara hachi bu” policy to eat only to 80% of stomach fullness as practiced by the long-lived Japanese on the island of Okinawa 74 ; Avoid habitual stomach overloading by overconsumption to prevent stomach hypertrophy 69 , 70 ; Be mindful of genetic obstacles to regulating body weight and body fat by substituting daily weighings of your body mass as a dependable low-tech feedback of management of energy balance 75 ; Incorporate deliberate physical activity (both aerobic locomotion and weight lifting) by embracing helpful technology of wearable activity monitors.…”
Section: Evidence-based Thesismentioning
confidence: 99%
“…Resist environmental pressure to overeat whether caused by social facilitation during holidays, highly palatable foods, or commercial pressure to eat oversized portions in restaurants 73 . Follow “hara hachi bu” policy to eat only to 80% of stomach fullness as practiced by the long-lived Japanese on the island of Okinawa 74 ;…”
Section: Evidence-based Thesismentioning
confidence: 99%
“…A leptina seria a nossa heroína, ela atua gerando o aumento da queima de energia e diminuindo a ingestão alimentar, consequentemente, favorecendo o emagrecimento, ou pelo menos, o não acúmulo de gordura (HALL e GUO, 2017). Em contrapartida, a grelina seria a nossa vilã, ela aumenta o apetite (BORER, 2021).…”
Section: Mas Afinal Por Que é Tão Difícil Emagrecer?unclassified